Survey of Public Participation in the Arts (SPPA), 2012 (United States) ([Verlag nicht ermittelbar], 2014)
This data collection is comprised of responses from two sets of survey questionnaires, the basic Current Population Survey (CPS) and a survey administered as a supplement to the July 2012 basic CPS questionnaire. The supplement, on the topic of public participation in the arts in the United States, was sponsored by the National Endowment for the Arts. The CPS, administered monthly, collects labor force data about the civilian noninstitutional population aged 15 years old or older living in the United States. Moreover, the CPS provides current estimates of the economic status and activities of this population which includes estimates of total employment (both farm and nonfarm), nonfarm self-employed persons, domestics, and unpaid helpers in nonfarm family enterprises, wage and salaried employees, and estimates of total unemployment. The basic CPS data are provided on labor force activity for the week prior to the survey. In addition, CPS provides respondents' demographic characteristics such as age, sex, race, marital status, educational attainment, family relationship, occupation, and industry. In addition to the basic CPS questions, interviewers asked supplementary questions on public participation in the arts of two randomly selected household members aged 18 or older from about one-half of the sampled CPS households. Interviews were conducted during the period of July 15-21, 2012. The supplement contained questions about the sampled member's participation in various artistic activities from July 1, 2011 through July 1, 2012. If the selected person had a spouse or partner, then the respondent answered questions on behalf of their spouse/partner. Therefore, the spouse/partner responses are proxies. If a respondent was answering for themselves and on behalf of their spouse or partner, the respondent and spouse/partner questions followed the same path through the instrument. Spouse/partner questions were asked on core participation (Core 1 or Core 2), leisure activities (Module D), and the first four questions of Module A. The total sample size of the 2012 SPPA was 35,735 American adults, ages 18 and over. The 2012 SPPA included two core components: a questionnaire used in previous years to ask about arts attendance; and a new, experimental module on arts attendance. In addition, the survey included five modules designed to capture other types of arts participation as well as participation in other leisure activities. Respondents were randomly assigned to either of the survey's core questionnaires, and then were randomly assigned to two of the remaining five SPPA modules. Questions were asked about the type of artistic activity, the frequency of participation, training and exposure, musical and artistic preferences, school-age socialization, and computer and device usage related to artistic information. The topics were separated into the five modules (each module was administered to only a portion of the sampled cases): Module A: Other Attendance and Music Preferences (reading, film, or sporting event attendance; other live performances; and music listening preferences) Module B: Accessing Art through Media (using media for participation in artistic events and frequency of participation in past year) Module C: Creating Arts through Media (participation in certain types of other leisure or artistic activities, public artistic performances, and using media to share activities in past year) Module D: Creating, Performing, and Other Activities (sport activities, other art activities, and musical performance activities in past year) Module E: Arts Learning (art related lessons or classes, respondent age during lessons/classes, location of lessons/classes, respondents' parents' education, and the participation of the respondents' school age children)